Quadrature Mirror Filter Bank Design for Mitral Valve Doppler Signal Using Artificial Bee Colony Algorithm - Koza, Turker; Karaboga, Nurhan (Elektronika ir Elektrotechnika, 2017)
In this paper, a new design method was developed for quadrature mirror filter (QMF) bank. Previous QMF bank design methods focused on frequency response properties such as pass band and stop band parameters with symmetrical filters. With the proposed method, QMF bank was designed using on time domain signals as mitral valve signal with unsymmetrical filter. The design problem was formulated as an objective function of difference between QMF bank’s input and output signals. QMF bank signal disparity was compared with correlation and peak reconstruction error (PRE). QMF bank prototype filter parameters were optimized with Artificial Bee Colony (ABC) and Differential Evaluation (DE) Algorithms. Design outputs were compared with previous works.DOI: http://dx.doi.org/10.5755/j01.eie.23.1.17584